The Effect of Chitosan in Feed on Growth, Survival Rate and Feed Utilization Efficiency of Nile Tilapia (Oreochromis niloticus) - Rozi Rozi; Akhmad Taufiq Mukti; Syifania Hanifah Samara; Muhammad Browijoyo Santanumurti (Jurnal Perikanan Universitas Gadjah Mada, 2018)
Chitosan is a functional polysaccharide that is capable of inducing various biological activities. This research aims to examine the effect of chitosan on growth and blood profile of tilapia fish. The method used in this research was experimental methods with completely randomized design (RAL) consisting of 4 treatments and 3 times. 120 Tilapia fish in 5-7 cm in range size were reared in aquarium at density of 10 fish/aquarium. Feedwere given at the additional dose of 10 ppt, 50 ppt, and 100 ppt chitosan. The observed variables were growth rate, survival rate, fish blood profile, water quality, feed utilization efficien . The results showed that the best chitosan treatment was at a dose of 100 ppt which produced FCR of 3.48 ± 2.25, AGP: 0.13 ± 0.03, SGR: 0.85 ± 0.84 and EPP: 28.70 ± 16,54.